Refinements of Hermite–Hadamard Inequalities for Continuous Convex Functions via (p,q)-Calculus - Julalak Prabseang; Kamsing Nonlaopon; Jessada Tariboon; Sotiris K. Ntouyas (Mathematics, 2021)
In this paper, we present some new refinements of Hermite–Hadamard inequalities for continuous convex functions by using <semantics>(p,q)</semantics>-calculus. Moreover, we study some new <semantics>(p,q)</semantics>-Hermite–Hadamard inequalities for multiple integrals. Many results given in this paper provide extensions of others given in previous research.